2005
DOI: 10.1186/1471-2458-5-108
|View full text |Cite
|
Sign up to set email alerts
|

Assessing immunization data quality from routine reports in Mozambique

Abstract: Background: Worldwide immunization coverage shows an increase in the past years but the validity of the official reports for measuring change over time has been questioned. Facing this problem, donor supported initiatives like the Global Alliance for Vaccine and Immunizations, have been putting a lot of effort into assessing the quality of data used, since accurate immunization information is essential for the Expanded Program on Immunization managers to track and improve program performance. The present artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
3
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 12 publications
(16 reference statements)
6
99
3
10
Order By: Relevance
“…Studies showed that data quality was poor in different settings like Mozambique and Kenya (Mavimbe, Braa & Bjune 2005;Odhiambo-Otieno 2005b). Similarly, use of information for planning and decision-making was found to be weak in Brazil (Da Silva & Laprega 2005).…”
Section: Previous Literaturesmentioning
confidence: 99%
“…Studies showed that data quality was poor in different settings like Mozambique and Kenya (Mavimbe, Braa & Bjune 2005;Odhiambo-Otieno 2005b). Similarly, use of information for planning and decision-making was found to be weak in Brazil (Da Silva & Laprega 2005).…”
Section: Previous Literaturesmentioning
confidence: 99%
“…1 However, the quality of the data produced by such systems is often poor and the data are not used effectively for decision-making. 2 Although there has been increasing international attention to the need to develop strong health information systems, it has proved difficult to do so for several reasons, including fragmentation and lack of coordination of health programmes and insistence by international agencies on maintaining their own vertical systems 3 ; lack of shared data standards 4 ; unrealistic ambitions 5 ; inability of system developers to handle complex organizational, social and cultural issues 6 ; and problems of sustainability. 7 The Health Metrics Network, established in 2005, has been instrumental in addressing the problem of fragmentation in health information systems through its technical framework, 8 which promotes a data warehouse approach to information system integration, 3,9 and in creating global consensus on the need for all actors to join forces and work towards integrated systems.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies are higher than those noted by Kayode et al [19] in Greater Accra, with a variation of 0.15% for deliveries and 1.05% for all registered persons. In Mozambique, a lower discrepancy (below 10%) than ours has been reported for immunization data between the register of health centers and district report [10].…”
Section: Accuracy Of Data Collected For Snigsmentioning
confidence: 53%
“…For instance in immunization programs, discrepancy between reported and actual coverage increased since GAVI started supporting health systems [9]. In Mozambique, one of the countries concerned, poor data quality affects each type of vaccine with a noted difference between the sheets score, records of service, and district reports [10].…”
Section: Introductionmentioning
confidence: 99%